(untitled) (Research, Society and Development, 2021)
The present study aimed to analyze intoxications in children and adolescents. This is a descriptive, retrospective study with a quantitative approach, carried out in a public tertiary hospital in the State of Ceará. The intoxication records of patients, suspected of acute poisoning by toxic agents, were evaluated in 2019. 959 records of patients aged <1 to 15 years were analyzed, and it was observed that there was no difference between males (50, 89%, n = 488) and the female (49.11%, n = 471). First, the age group between 1 and 5 years, responsible for 43.80% (n = 420) of the cases, in second place, from 6 to 10 years with 27.84% (n = 267), third place of 11 to 15 years old with 26.80% (n = 257), and in the fourth and last <1 year of age with 1.56% (n = 15). In relation to toxic agents, scorpionism were the most prominent, 78.62% (n = 754) of the cases, followed by drugs with 6.05% (n = 58), venomous venomous animals (snakes) with 3.23% (n = 31), non-venomous animals with 2.92% (n = 28), industrial chemicals 2.61% (n = 25) and household cleaning products with 1.25% (n = 12). With regard to accidents involving venomous animals, 80.65% (n = 25) of the cases were caused by snakes, 1.72% (n = 13) by scorpions and 33.33% (n = 2) by spiders, requiring in some cases the use of antidotes. It is concluded that accidents involving children and adolescents are becoming more and more frequent, which promotes the need for campaign strategies for greater guidance, monitoring and psychological help in schools, public spaces and the internet.